Pancasila and Islamic Religious Education as Philosophical Paradigms: Reconstructing Human Rights in Indonesia through Islamic Sociological Jurisprudence Theory - Ahmad Muhamad Mustain Nasoha; Elsya Novitasari Anggraini; Ratna Ayu Fitriana; Rahmania Nur Aslami (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study analyzes the reconstruction of Human Rights (HR) in Indonesia through the integration of Pancasila values and Islamic Religious Education (IRE) within the framework of Islamic Sociological Jurisprudence. In the Indonesian context, human rights are not merely perceived as universal individual liberties, but are understood within broader philosophical, religious, and socio-cultural dimensions. Pancasila functions as the foundational framework that harmonizes individual rights with social responsibilities, while Islamic teachings provide normative and theological foundations through principles such as maqasid al-shari‘ah, justice (‘adl), and human dignity (karamah insaniyyah), as well as Qur’anic values of tolerance and moderation (tasamuh and wasatiyyah). This research adopts a qualitative method with a descriptive approach based on literature review, drawing upon various scholarly sources related to human rights, Islamic education, and sociological jurisprudence. The findings reveal that the integration of Pancasila and Islamic Religious Education generates a comprehensive understanding of human rights that is both normative and contextual. Moreover, empirical findings indicate that a deeper comprehension of Qur’anic teachings on tolerance is positively correlated with the development of moderate and inclusive attitudes, thereby highlighting the significant role of education in internalizing human rights values. Additionally, the historical transition from pre-Islamic (Jahiliyyah) society to the Islamic era demonstrates that Islamic teachings function as an agent of social transformation by promoting justice, equality, and the protection of marginalized groups. From the perspective of Islamic Sociological Jurisprudence, law is viewed as a dynamic system that must remain responsive to evolving social conditions, ensuring that the reconstruction of human rights remains relevant and adaptable. In conclusion, the synergy between Pancasila values, Islamic teachings, and sociological legal approaches contributes to the formation of a more inclusive, balanced, and culturally grounded human rights paradigm in Indonesia.